Konsep dan Aplikasi Sukuk Negara dalam Pembiayaan Defisit APBNdi Indonesia - Arie Rachmat Soenjoto; Hilda Lutfiani (University of Darussalam Gontor, 2016)
Increasing government expenditure which is not accompanied by increasing country Income can cause an enhancement State Budget deficit, so far, the government still fond to cover up budget deficit with foreign debt, where foreign debt is never apart from the interest as of the loan. Therefore, alternative way accordance with the principles of shari’ah which can become a source of financing of the state budget deficit need to issued. This research aims to know more in the concept of the sovereign sukuk issuance in state budget financing and to discover position of sovereign sukuk in state budget deficit in Indonesia. this research use literature study. To discuss more in and achieve the goal, attempting to collect data both primary and secondary. The processingof collecting data method of observation which is the first step to see and get the necessary data with how to observethe intensively books and other data source. Then analyzed using the way of thinking of the induction-deductions method to draw a conclusion. In order to analyze which conveyed more depth, continued analysis usingdescriptive analysis techniques analysis. This research results that sovereign sukuk potential to be developed as an alternativein accordance withthe principles of shari’ah which can become a source of financing the deficit with 3 publishing mechanism, namely Private placement, book building and auction. Position of sovereign sukuk in state budget deficit in 2010- 2014 is not clear because the deficitincrease from IDR 46.8 Trillion to IDR 241.5 Trillion, but in 2014- 2015 budget deficit decrease from IDR 241.5 Trillion to IDR 222.5 Trillion, while the financing of thestate budget deficit sourcefrom the issuance of the sovereign sukuk on2014-2015 experiencing an increaseof IDR 265 Trillion to IDR 298 Trillion, that the allocationslook more detailed, transparent and orderly manner . And willreducethe budget deficit.